Erving Goffman and the Cold War - Jaworski, Gary D. (Lexington Books, 2023)
Erving Goffman and the Cold War presents a provocative new reading of the work of sociologist Erving Goffman. Instead of viewing him as a “marginal man” or academic outsider, Gary D. Jaworski explores Goffman as a social theorist of the Cold War. Goffman was deeply connected to both the ethos of his time and to a range of cold warriors and their critics, such as Edward A. Shils, Thomas C. Schelling, and the researchers on “brainwashing” associated with the Walter Reed Army Institute of Research, among others. Chapters on loyalty, betrayal, secrecy, strategy, interrogation, provocation, and aggression concretely illustrate these connections. Erving Goffman and the Cold War shows that Goffman was much more than a microsociologist of mundane life; he was a perceptive analyst of the Cold War America.